2018
DOI: 10.1016/j.ijheatmasstransfer.2017.12.093
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation into the inclination effect on conjugate pool boiling and the condensation of steam in a passive heat removal system

Abstract: In this study, the effect of the tube inclination angle on simultaneous condensation inside and pool boiling outside a smooth tube is investigated numerically. Such conjugate phase-change phenomena happen in many heat exchangers, particularly in passive heat removal systems. The simulated domain is a pool filled with water liquid at atmospheric pressure, with a submerged tube with inner and outer diameters of 19 mm and 25 mm respectively. The fluid inside the tube is considered to be the steam at the saturatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Where δt denotes the time scale set to 0.05 [27][28]. The correlation of Ranz and Marshall [46] is used for computing the Nul at the interface as:…”
Section: Rpi Boiling Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…Where δt denotes the time scale set to 0.05 [27][28]. The correlation of Ranz and Marshall [46] is used for computing the Nul at the interface as:…”
Section: Rpi Boiling Modelmentioning
confidence: 99%
“…In contrast to well-established, longstanding experimental studies, the numerical simulation of pool boiling on heated surfaces is still in development [18]. [28] concluded that there will be a region between 30° to 60° for the inclination angle. In the experimental work of Kang [16], which is selected as the base database for the present work the optimum inclination angle was found to be 30°.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Phase change heat transfer with high heat flux, small heat dissipation area, and low working temperature, is a very efficient method compared with the single-phase heat transfer. Until now, many experimental studies on passive technologies, such as mixture fluid [1], nanofluids [2][3][4][5], surface modification [6,7], and simulation work [8] in relation to passive technologies have been performed to enhance pool boiling heat transfer. Meanwhile, pool boiling in different gravity conditions has been investigated in the last decade by numerous researchers [9][10][11][12][13][14][15], and there are many review papers regarding pool boiling in microgravity [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%